ANALISIS PEMANFAATAN LAHAN PEKARANGAN DI DESA SIDOMULYO KECAMATAN LIRIK KABUPATEN INDRAGIRI HULU - Chanlis Ozi Harsakti; Eri Sayamar; Yulia Andriani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aims to (1) find out the characteristics of the society of the utilization yard in Sidomulyo Village, Lirik subdistrict, Indragiri Hulu District (2) to find out the pattern of the yard Sidomulyo Village, Lirik subdistrict, Indragiri Hulu District. This research was conducted in Sidomulyo Village, Lirik subdistrict, Indragiri Hulu District, from Januari 2018 to November 2018 using snowball sampling. The number of samples in this study amounted to 25 people, where all samples used the yard. Data analysis used in this study is descriptive analysis. The results of this study indicate: (1) The Characteristics that influence the society in the used of yard are age, sex, education, income, and dependents of family, (2) The pattern of yard use of respondents in Sidomulyo Village is that the whole uses a horizontal pattern (100%) and there were no respondents in Maharatu Village who used the verticulture patternKeywords: yard, Society, yard pattern.